Cobalt and nitrogen-doped carbon catalysts for enhanced oxygen reduction and power production in microbial fuel cells. (1st September 2017) - Tang, Xinhua; Ng, How Yong
Highlights: Cobalt and nitrogen-doped carbon (CoNC) was synthesized to catalyze ORR in microbial fuel cell (MFC). CoNC exhibited a remarkable catalytic activity, predominant four-electron reaction, and excellent stability. CoNC prepared at 900 °C generated 13.3% higher maximum power density than Pt/C in MFC. The highly microporous structure and the cobalt coordinated by pyridinic nitrogen governed the ORR performance in MFC. Abstract: Cathodic oxygen reduction reaction (ORR) is essential for the performance of microbial fuel cell (MFC). Cobalt and nitrogen-doped carbon (CoNC) was synthesized to catalyze ORR in MFCs. CoNC prepared at 900 °C (CoNC-900) exhibited a remarkable catalytic activity (4.3% smaller compared with state-of-the-art Pt/C for reduction current density), predominant four-electron reaction with electron transfer number as high as 3.96, and excellent stability (5.5% lesser after 10 000 cycles for reduction current density). The maximum power density of the CoNC-900 MFC was 13.3% higher than that of Pt/C MFC. Long term operation tests showed that CoNC-900 MFC was very stable. The unprecedented performance of CoNC for ORR was attributable to the highly microporous structure and the cobalt coordinated by pyridinic nitrogen. This work demonstrates that CoNC is a very promising catalyst toward ORR in MFCs.